Мультимедійне забезпечення задач проектування систем дистанційного навчання - Щербина, О. А. (ХНУРЕ, 2024)
The work is devoted to study software tools that allow create multimedia educational systems, the most attractive of which is Camtasia Recorder and Sony Vegas Pro. The paper is concerned with functionality and capabilities of them. In detail describes the methodology example for creating multimedia educational systems and analyzes problems associated with this
Keywords: дистанційне навчання; multimedia educational systems